Biohazard and dynamic features of different polar compounds in vegetable oil during thermal oxidation - Yuan, Liyang; Xu, Ziyang; Tan, Chin Ping; Liu, Yuanfa; Xu, Yong Jiang (Elsevier, 2021)
Total polar compounds (TPC) have been considered as one of the most objective indicators for the evaluation of deterioration of deep-frying oils. However, the cytotoxic and dynamics features of different parts of polar compound were underestimated. The present study investigated the biohazard effect of different polar compounds from heated oils. The results indicated oxidize triglycerides monomer (ox-TGM) exhibited the most serious deleterious effect on THLE-2 cell viability, followed by triglycerides polymer (TGP) and degradation products. The investigation of polar compounds variation revealed that vegetable oil with higher saturation endured longer thermal oxidation time to achieve the discarded point of 27% TPC. As the increase of thermal oxidation time, the content of polymers and oxidized products increased linearly, while the level of degradation products was altered moderately. The canonical correspondence analysis uncovered significant positive associations between oleic acid and ox-TGM at the initial stage of thermal oxidation. Taken together, our overall findings offer an evidence that ox-TGM could be acted as an accurate indicator for the evaluation of deep-frying oil quality.